Palladium-catalyzed C–N and C–O bond formation of N-substituted 4-bromo-7-azaindoles with amides, amines, amino acid esters and phenols - Surasani, Rajendra; Kalita, Dipak; Rao, A. V. Dhanunjaya; Chandrasekhar, K. B. (Beilstein Journal of Organic Chemistry, 2012)
Simple and efficient procedures for palladium-catalyzed cross-coupling reactions of N-substituted 4-bromo-7-azaindole (1H-pyrrole[2,3-b]pyridine), with amides, amines, amino acid esters and phenols through C–N and C–O bond formation have been developed. The C–N cross-coupling reaction of amides, amines and amino acid esters takes place rapidly by using the combination of Xantphos, Cs2CO3, dioxane and palladium catalyst precursors Pd(OAc)2/Pd2(dba)3. The combination of Pd(OAc)2, Xantphos, K2CO3 and dioxane was found to be crucial for the C–O cross-coupling reaction. This is the first report on coupling of amides, amino acid esters and phenols with N-protected 4-bromo-7-azaindole derivatives.
Keywords: 7-azaindole; C–N bond; C–O bond; ligand; palladium catalyst